ANALISIS PENGGUNAAN E-MODUL BERBASIS KETERAMPILAN SOSIAL BERORIENTASI JAGUNG PADA PEMBELAJARAN IPA SD DI SDN 1 PROPPO PAMEKASAN - Fena Emilda, Ayik; Fadlillah, M. (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research aims to analyze the use of corn-oriented social skills-based e-modules in elementary school science learning. Where in this research there are two problems, namely how the attractiveness of e-modules is proven by teacher and student questionnaire responses and how students understand science learning using electronic-based modules. This research uses qualitative research methods using descriptive research carried out at SDN 1 Proppo Pamekasan. The subjects in this research were class V students at SDN 1 Proppo Pamekasan, with a total of 16 students. 11 male students and 5 female students. Researchers used data collection techniques through observations, interviews and questionnaires. The data obtained by researchers is that students need digital-based teaching materials, namely electronic modules that support students to learn. The attractiveness of using E-Modules as proven by the student response questionnaire obtained a percentage result of 90% and the teacher percentage results obtained 100%. It can be concluded that E- The module can be said to be interesting and usable. Student learning outcomes after using corn-oriented social skills-based e-modules in elementary science learning show classical completion criteria, namely ≥ 85% of students reach the KKM.